Impact of Reperfusion for Nonagenarians Treated by Mechanical Thrombectomy: Insights From the ETIS Registry. Issue 11 (November 2019) - Drouard-de Rousiers, Eve; Lucas, Ludovic; Richard, Sébastien; Consoli, Arturo; Mazighi, Mikaël; Labreuche, Julien; Kyheng, Maéva; Gory, Benjamin; Dargazanli, Cyril; Arquizan, Caroline; Marnat, Gaultier; Blanc, Raphaël; et al.
Abstract : Background and Purpose—: Nonagenarians represent a growing stroke population characterized by a higher frailty. Although endovascular therapy (ET) is a cornerstone of the management of acute ischemic stroke related to large vessel occlusion, the benefit of reperfusion among nonagenarians is poorly documented. We aimed to assess the impact of ET-related reperfusion on the functional outcome of reperfusion in this elderly population. Methods—: A retrospective analysis of clinical and imaging data from all patients aged over 90 included in the ETIS (Endovascular Treatment in Ischemic Stroke) registry between October 2013 and April 2018 was performed. Association between post-ET reperfusion and favorable (modified Rankin Scale [0–2] or equal to prestroke value) and good (modified Rankin Scale [0–3] or equal to prestroke value) outcome were evaluated. Demographic and procedural predictors of functional outcome, including the first-pass effect, were evaluated. Results were adjusted for center, admission National Institutes of Health Stroke Scale, and use of intravenous thrombolysis. Results—: Among the 124 nonagenarians treated with ET, those with successful reperfusion had the lowest 90-day modified Rankin Scale (odds ratio, 3.26; 95% CI, 1.04–10.25). Only patients with successful reperfusion after the first pass (n=53, 56.7%) had a reduced 90-day mortality (odds ratio, 0.15; 95% CI, 0.05–0.45) and an increased rate of good outcome (odds ratio, 4.55; 95% CI, 1.38–15.03). No increase in the rate of intracranial hemorrhage was observed among patients successfully reperfused. Conclusions—: Successful reperfusion improves the functional outcome of nonagenarians who should not be excluded from ET. The first-pass effect should be considered in the procedural management of this frail population. Abstract : Supplemental Digital Content is available in the text.